A Comparative Performance Appraisal of VFPCK and Kudumbashree beneficiaries in TVM District - Shruthi K.Soman (Department of Agricultural Economics, College of Agriculture, 2012)
The study entitled “A comparative performance appraisal of VFPCK and Kudumbashree beneficiaries in Thiruvananthapuram district” was undertaken in Nemom block of Thiruvananthapuram district with the objective to compare the performances of VFPCK farmers, Kudumbashree farmers and other farmers in terms of agricultural production, income generation, expenditure, savings pattern, credit utilization and marketing. It also aimed at identifying the constraints faced by the farmers in production and marketing. The required information was collected from 30 each of randomly selected VFPCK, Kudumbashree and other farmers so as to make the total sample size 90. Culinary melon and cowpea which were the two major vegetables grown in the study area were used to compare the production, cost of cultivation and resource use efficiency of the three categories of farmers. A noteworthy feature of the study area is that almost all farmers cultivated in leased land. In the present study cost of cultivation was worked out using A B C cost concepts and resource use efficiency was estimated using Cobb- Douglas production function. Marketing channels of the three categories of farmers were identified and the price spread and efficiency of channels were calculated. Credit utilization, expenditure and savings pattern were also worked out and constraints were ranked using Garrett’s ranking technique. The total cost of cultivation of cowpea calculated on per hectare basis revealed that it was the highest for VFPCK farmers followed by other farmers and Kudumbashree farmers. Cost A2 was estimated as Rs.1,10,150, Rs.54,968 and Rs.1,25,532 per hectare and Cost C3 was estimated as Rs.3,30,613, Rs.2,95,422, and Rs.3,65,867 per hectare respectively for VFPCK, Kudumbashree and other farmers. Labour accounted for 31 per cent of Cost A2 of VFPCK farmers followed by manures (23 per cent) while for Kudumbashree farmers 39 per cent of Cost A2 was contributed by panthalling material and 30 per cent by manures. For other farmers, also, hired labour contributed the major share of Cost A2 (41 per cent) followed by manures (17 per cent). In culinary melon cultivation, Cost A2 per hectare was the highest for other farmers (Rs.84,650), followed by the VFPCK farmers ( Rs.73,438) and Kudumbashree farmers (Rs.32,326). Cost C3 also followed the same trend and was the highest for other farmers (Rs.2,99,004 per hectare) followed by VFPCK farmers (Rs.2,96,223 per hectare) and Kudumbashree farmers (Rs.1,88,389 per hectare). For VFPCK farmers, hired labour accounted for 30 per cent of Cost A2 followed by rent of leased land at 13 per cent while for Kudumbashree farmers, manures (50 per cent) occupied the largest share followed by rent of leased land (22 per cent). For other farmers, labour accounted the major share of Cost A2 (34 per cent) followed by manures (29 per cent). The yield of cowpea was found to be the highest for VFPCK farmers (12,661 kilograms) followed by other farmers (11,007 kilograms) and Kudumbashree farmers (5,215 kilograms). The corresponding gross returns obtained by the three categories of farmers were Rs 4,43,135, Rs 1,82,525 and Rs 3,85,245 per hectare at an average market price of Rs 35 per kilogram. For culinary melon, the highest yield was obtained by other farmers (20,767 kilograms), followed by VFPCK farmers (18,320 kilograms) and the lowest yield was obtained by Kudumbashree farmers (5,817 kilograms). The corresponding gross returns per hectare obtained by the three categories of farmers were respectively Rs.2,07,670, Rs.1,83,200 and Rs.58,170 per hectare at a market price of Rs. 10 per kilogram. The cost of production per kilogram of cowpea was the lowest for VFPCK farmers (Rs. 26.11 per kilogram), followed by other farmers (Rs.33.24 per kilogram) and it was the highest for Kudumbashree farmers (Rs.56.65 per kilogram) at Cost C3 level. The cost of production per kilogram of culinary melon was the lowest for other farmers (Rs.14.39 per kilogram) followed by VFPCK farmers (Rs.16.16 per kilogram) and the highest for Kudumbashree farmers (Rs. 32.38 per kilogram). The production function analysis revealed that expenditure on plant protection chemicals had a significant impact on returns of VFPCK farmers in the case of cowpea while manures showed a positive and significant impact on returns of Kudumbashree farmers. For the other farmers, area had a positive and significant positive impact on returns, while plant protection chemicals had a negative and significant impact. The production function analysis of culinary melon revealed that, for VFPCK farmers and other farmers, area had a significant impact on returns while for the Kudumbashree farmers, human labour had a significant positive impact on returns. Among the VFPCK farmers, indebtedness was 76 per cent while it was 70 per cent for Kudumbashree and about 73 per cent for others. Average annual income was the highest for VFPCK farmers followed by the other farmers and was the lowest for Kudumbashree farmers. The largest item of consumption expenditure for all the categories of farmers was food which varied from 31 per cent for VFPCK farmers to 38 per cent for other farmers. Four marketing channels were identified in the study area for vegetables of which channel-I was found to be the most efficient one whereas the net price received by the farmer was highest in channel- III. The important constraints identified using Garrett’s ranking technique were, pests and diseases, water inundation and high costs of labour and inputs for all the categories of farmers.